Results from the Department of Mathematical Cybernetics in the Field of Discrete Structures and Algorithm Complexity - Alekseev, V. B.; Marchenkov, S. S.; Selezneva, S. N. (Moscow University computational mathematics and cybernetics, 2024)
The author presents some of the most important results obtained at the Department of Mathematical Cybernetics by Profs. V.B. Alekseev, S.S. Marchenkov, S.N. Selezneva, and their post- and graduate students since the start of the 21st century.